3(3+x)=2x+4

Simple and best practice solution for 3(3+x)=2x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3+x)=2x+4 equation:


Simplifying
3(3 + x) = 2x + 4
(3 * 3 + x * 3) = 2x + 4
(9 + 3x) = 2x + 4

Reorder the terms:
9 + 3x = 4 + 2x

Solving
9 + 3x = 4 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
9 + 3x + -2x = 4 + 2x + -2x

Combine like terms: 3x + -2x = 1x
9 + 1x = 4 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 + 1x = 4 + 0
9 + 1x = 4

Add '-9' to each side of the equation.
9 + -9 + 1x = 4 + -9

Combine like terms: 9 + -9 = 0
0 + 1x = 4 + -9
1x = 4 + -9

Combine like terms: 4 + -9 = -5
1x = -5

Divide each side by '1'.
x = -5

Simplifying
x = -5

See similar equations:

| -40+n=8(8n-5) | | 2.5(x-3)-3+1.7x=10.8(x+1.5) | | (6y^1/2)/(x^4/3)=(12y/x^1/3) | | 5x+8-x=6(x-1) | | -1/9(-3/4)= | | 5m-3/2=6 | | (x^3)+(3x^2)+(-9x)-(12)=0 | | (x^3)+(3x^2)+(-4x)-(12)=0 | | y=-cos(5x) | | (x^3)+(3x^2)+(4x)-(12)=0 | | 9q-(q-4)=4q+(q+1) | | 7m^2=-6-17m | | (x^3)+(3x^2)+(-6x)-(12)=0 | | m-14=n | | (x^3)+(3x^2)+(6x)-(12)=0 | | (x^3)+(3x^2)+(Kx)-(12)=0 | | 3(z+6)=2(z-3)+z | | 6x-36=10x+5 | | -14=-4(8x-8)-7(6x-4) | | -4-40k=-4.5-39k | | -9.5a-6+12a=-2 | | x-1/2×1/2=1/8 | | C(10,2)=10!/(10-2)!) | | x^(2/5)-2x(1/5)-15=0 | | 15z-9-8z-4=5z-2 | | 9.1=((x-73.1)^2)/4 | | 10x-25=9x+20 | | 5q=(23/3) | | 3+48=m+3 | | 5(7n-8)+2(n+2)=75 | | (23/3)/5= | | (x+y)-(3x+y)= |

Equations solver categories